Experimental research method for exploring influence of bolt fastening behavior in proton exchange membrane electrolytic cell on performance of proton exchange membrane electrolytic cell based on transparent visual system
Through experimental research methods based on transparent visualization system, the impact of bolt tightening behavior on performance in PEMEC was explored, and the problem of insufficient research on bolt tightening behavior in the prior art was solved, and the optimization of PEMEC performance and extension of life was achieved.
Patent Information
- Application Number
- CN202510102360.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, there are few studies on the impact of the bolt tightening behavior of PEMEC on its performance, resulting in an increase in contact resistance and affecting the performance and life of PEMEC.
Using an experimental research method based on a transparent visualization system, the pressure distribution is measured by pressure sensitive paper, the pressure map is converted by high-definition scanner and image processing technology, and the two-phase flow distribution is recorded in combination with a high-speed camera to study the influence of bolt torque, tightening steps, and tightening sequence on PEMEC performance.
Through the experimental system, the electrochemical performance, local current distribution and pressure distribution are linked to evaluate the impact of bolt operating conditions, and the minimum bolt torque, optimal tightening steps and optimal installation sequence of PEMEC are proposed to improve the performance and life of PEMEC.
Smart Images

Figure CN119880238A_ABST
Abstract
Description
[0001] The invention belongs to the technical field of proton exchange membrane electrolyzer performance optimization research, and specifically relates to an experimental research method for exploring the influence of bolt tightening behavior in a proton exchange membrane electrolyzer on its performance based on a transparent visualization system. Background Art
[0003] With the development of the global economy and society, people's demand for energy has been rising year by year. The extensive use of fossil energy has caused frequent problems such as global warming, environmental degradation, and energy crises. There is an urgent need to find a carbon-free energy source to support the development of future energy. Hydrogen energy, as a green and efficient secondary energy source, can well realize energy conversion and is widely used in construction, steel, aerospace, high-end manufacturing and other fields to achieve deep decarbonization. PEMEC has become a promising technology for hydrogen production by electrolysis of water because of its ability to quickly adapt to fluctuations in renewable energy output. In order to improve the working efficiency of PEMEC, in-depth research is mainly carried out through the development of new catalysts, the development of high-performance materials, the search for optimal operating conditions, the design of internal structures, and the optimization of manufacturing processes.
[0004] The common PEMEC structure is composed of two plates, two diffusion layers and a membrane electrode (MEA) assembled in a symmetrical structure, and the flow channel is usually designed on the bipolar plate. After assembly, the components are locked together by bolts, and gaskets need to be added between the components to improve the sealing. Multi-bolt connection is a key component of PEMEC. The bolt tightening method directly affects the force distribution at the end of the bolt, which in turn affects the contact resistance of the equipment. In order to reduce the contact resistance, sufficient pressure needs to be maintained between the components in PEMEC. However, due to processing errors, uneven gasket thickness, rough material surface, and non-fitting of components, the contact surface is uneven, causing the contact resistance to increase, further affecting the performance and life of PEMEC. The behavior of the bolt becomes a key factor affecting the performance and life of PEMEC, and the size of the bolt torque directly affects the clamping pressure of each PEMEC component. Uniform pressure distribution and close contact between components are the ultimate goals of PEMEC bolt installation research, and a comprehensive analysis of the bolt installation process is required.
[0005] So far, there are few studies on the effects of bolt torque, clamping pressure, and gasket materials on PEMEC performance. Therefore, the present invention adopts a visual experimental system, considers bolt operation, pressure distribution, and two-phase flow characteristics, and conducts research on the effects of bolt torque, tightening steps, and bolt installation sequence on PEMEC performance. The purpose is to link the electrochemical performance, local current distribution, and pressure distribution through an experimental system under different torques and different installation sequences, so as to evaluate the effects of bolt operation conditions. Based on the experimental research results, the minimum bolt torque, optimal tightening steps, and optimal installation sequence of PEMEC are proposed.
[0006] This invention is the first to introduce the installation sequence into the study of PEMEC, and it is also the first time to use transparent PEMEC to evaluate the impact of different bolt operating conditions on PEMEC performance, which has good reference significance. In addition, this invention is an effective supplement to the existing research. The experimental results are expected to better understand the changes in PEMEC performance and internal mass transfer under different bolt operating conditions, and provide data reference and experimental support for researchers who subsequently study high-performance PEMEC and PEMEC internal mass transfer. Summary of the invention
[0008] Purpose of the invention: In order to explore the influence of bolt tightening behavior on PEMEC performance, an experimental research method based on a transparent visualization system is proposed to explore the influence of bolt tightening behavior in proton exchange membrane electrolyzer on its performance.
[0009] In order to achieve the above object, the present invention adopts the following technical solution: an experimental research method for exploring the influence of bolt tightening behavior in PEMEC on its performance based on a transparent visualization system, comprising the following steps:
[0010] S1: First, the pressure distribution between the gas diffusion layer and MEA of PEMEC under different experimental conditions was measured by pressure-sensitive paper. The pressure map of the pressure-sensitive paper was converted into two-dimensional and three-dimensional pressure cloud maps using high-definition scanners and image processing technology. The effects of bolt torque, tightening steps, and tightening sequence on the contact resistance of PEMEC were studied through three-dimensional pressure cloud maps.
[0011] S2: Then the two-phase flow distribution generated by the high-speed camera in the same time period is intercepted and combined with the two-dimensional pressure cloud map to verify the influence of bolt torque, tightening steps and tightening sequence on the electrochemical performance of PEMEC;
[0012] S3: Based on the above research, the current density and voltage of the whole PEMEC are measured, the PEMEC polarization curve is drawn, and then the optimal torque, the most appropriate number of tightening steps, and the most appropriate tightening sequence of the bolt are determined based on the experimental data.
[0013] Specifically, the experimental details are as follows:
[0014] S1: Electrolyzer unit: Visualization PEMEC is the core component of the experimental platform, mainly composed of end plates, transparent plates, current collectors, diffusion layers, membrane electrodes, bolts, gaskets and other components. It is fixed by 8 symmetrically distributed M6 hexagonal bolts. The bolts are made of SCM435 alloy steel, with a tensile strength of 1220MPa, a nominal torque of 15-20N·m, and a standard verification load of 830MPa. Its assembly diagram is shown in the figure below. Figure 1As shown. The PEMEC end plate is made of stainless steel with an observation window. The size of the end plate is 100 mm×100 mm, and the size of the observation window is 50 mm×50 mm. The transparent plate is made of acrylic plate material. The gas-liquid two-phase flow state in the electrolytic cell can be observed through the observation window on the end plate and through the transparent plate. The current collecting plate is made of pure titanium plate with mirror treatment, which has good corrosion resistance and conductivity. A serpentine flow channel with a width of 1 mm is engraved on the titanium plate. Titanium felt is used as the gas diffusion layer of the cathode and anode, wherein the anode side has a 0.5 μm thick iridium coating and the cathode side has a 0.5 μm thick platinum coating. The proton exchange membrane uses Nafion117 membrane with a membrane size of 50 mm×50 mm×0.17 mm. 2.0 mg / cm 2 of iridium dioxide and 2.5 mg / cm 2 of platinum as a catalyst.
[0015] S2: Experimental test bench: It is mainly composed of PEMEC, water bath, peristaltic pump, high-speed camera, power supply, digital torque wrench and gas-liquid separator. Data collection and parameter control can be performed through the host computer. The water bath is used to control the temperature of the circulating water flow. The model is HH-2 double hole. Its heating temperature range is 10 ℃-100 ℃, and the temperature fluctuation is less than 0.1 ℃. The peristaltic pump is used to provide PEMEC water flow input. The model is BT100, and its flow range is 0.002-570 mL / min. The digital torque wrench is used to adjust the bolt torque. Its model is KPD-10, with a working range of 0.5~10 N·m and an accuracy of ±0.1N·m. The high-speed camera used in the experiment has 240 fps and 1.3 million pixels, which is used to record bubbles and bubble distribution during the torque experiment. The system power supply is a programmable DC power supply, model SS-K1560SP 15V 60A, output voltage 0~15V, voltage resolution 1 mV, output current 0~60 A, current resolution 1 mA. This power supply can record polarization curves without using an additional voltmeter or ammeter. To ensure the normal operation of PEMEC, water will be passed through the anode and cathode at the same time. The gas-liquid separator can separate the gas-liquid mixture discharged from PEMEC, and the liquid will flow back to the water bath for circulation.
[0016] The beneficial effects of the present invention are:
[0017] (1) The present invention provides an experimental research method for exploring the influence of bolt tightening behavior on the performance of PEMEC based on a transparent visualization system, which can provide data reference and experimental support for researchers who conduct subsequent research on high-performance PEMEC and internal mass transfer of PEMEC.
[0018] (2) The present invention provides an experimental research method based on a transparent visualization system to explore the effect of bolt tightening behavior on the performance of PEMEC. It explains the relationship between the tightening of bolts and the electrochemical performance of PEMEC, and shows the relationship between bolt tightening and the gas-liquid two-phase flow state inside PEMEC. The research results can provide a reference for the optimization of PEMEC assembly and installation processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is an assembly diagram of a PEM electrolyzer in the present invention; Figure 2 It is a connection diagram of the experimental system in the present invention; Figure 3 1. The pressure diagram of the electrolyzer and the two-phase flow state diagram under different torques in the embodiment; Figure 4 is the polarization curve of the electrolytic cell under different torques in the embodiment; Figure 5 is the bolt number and tightening sequence in the embodiment; Figure 6 is the definition of the number of tightening steps in the embodiment; Figure 7 : is the electrolytic cell pressure diagram and two-phase flow state diagram under different tightening steps in the embodiment; Figure 8 is the polarization curve of the electrolytic cell at different tightening steps in the embodiment; Fig. 9 is the definition of different tightening sequences in the embodiments; Fig.10 It is a different tightening sequence arrangement in the embodiment; Fig.11 1. The pressure diagram of the electrolytic cell and the two-phase flow state diagram under different tightening sequences in the embodiment; Fig.12 1 is the polarization curve of the electrolytic cell under different tightening sequences in the embodiment. DETAILED DESCRIPTION
[0021] In order to explain the technical solution of the present invention in detail, the following is further described in conjunction with the drawings and specific embodiments of the specification. It should be understood that the described embodiments are only used to explain the present invention and are part of the embodiments of the present invention, rather than all of the embodiments.
[0022] S1: Experimental process and precautions: Before each experiment, the PEMEC was preheated for 30 min to reduce the effects of cold start and membrane drying on electrochemical performance. In addition, the water inlet and outlet temperatures need to be measured simultaneously during preheating to ensure that the internal temperature of the system is constant. When the system is relatively stable, current begins to be supplied to the PEMEC.
[0023] S2: During the operation of PEMEC, after adjusting the voltage of the electrolyzer, the current usually takes a long time to return to stability. Therefore, when doing each set of experiments, wait for the current to stabilize before recording the data and proceeding to the next step. To ensure the accuracy and repeatability of the experiment, each set of experiments was performed three times and the average was taken.
[0024] S3: In order to study the influence of bolt torque, tightening steps and tightening sequence on the electrochemical performance of the electrolytic cell, during the experiment, according to different bolt operation methods, the voltage and current values of the electrolytic cell after stabilization were recorded, and the electrochemical curve of the electrolytic cell was drawn through the data. Finally, the optimal torque of the bolt, the most appropriate tightening steps and the most appropriate tightening sequence were determined based on the experimental data.
[0025] S4: Pressure distribution measurement and image analysis: Pressure distribution measurement mainly uses pressure-sensitive paper to realize local pressure visualization. The pressure-sensitive paper used in the experiment has a range of 0-5 MPa and a thickness of about 0.2 mm, which can replace the membrane electrode relatively well. After each set of pressing experiments, the pressure-sensitive paper is converted into an electronic image using a high-definition scanner. The electronic image is grayed out using MATLAB software to read the grayscale value of each pixel. The grayscale value data is imported into Origin software to draw two-dimensional and three-dimensional pressure cloud maps. At the same time, a pressure color bar legend is drawn according to the matching of pressure and grayscale value.
[0026] S5: Optical visualization analysis of gas-liquid two-phase flow: For high-speed camera photography, different experimental groups were at 1.0 A / cm 2 Under the conditions of current density and water flow rate stopping, the picture taken 1.5 s after the bubbles emerge is taken as a reference object. The high-speed visualization system can intuitively display the advantages and disadvantages of the local performance of the electrolytic cell. In the location where the local performance of the electrolytic cell is good, the reaction is relatively violent and more bubbles are generated; on the contrary, in the area where the reaction is relatively gentle, fewer bubbles are generated, and even no bubbles can be observed. Using this method, it can be compared with the test results of pressure-sensitive paper to further study the effects of bolt torque and installation method on the local electrochemical performance of the electrolytic cell.
[0027] S6: Effect of different torques: In order to study the effect of different bolt torques on the performance of the electrolyzer, the sealing of the electrolyzer was tested in the early stage of the experiment. The torque experiment set the water temperature to 60 ℃ and the flow rate to 10 mL / min. The bolt torque was steadily increased from 0 N·m to 0.5 N·m. The leakage around the electrolyzer was observed while the torque was added. At the beginning of the operation, the leakage was obvious. As the torque increased, the leakage gradually weakened. When it was increased to 1.5 N·m, there was no obvious leakage, and there was slight wetness after running for 1 hour. The torque was increased to 2.0 N·m, and there was no leakage after running for 4 hours, indicating that 2.0 N·m was the minimum torque for the experimental system to not leak, and the sealing requirements were met. The torque set in the experiment will increase from 2.0 N·m, and there are seven different torques, namely 2.0 N·m, 2.5 N·m, 3.0 N·m, 3.5 N·m, 4.0 N·m, 4.5 N·m, and 5.0 N·m. Pressure-sensitive paper was used to record the contact pressure between the gas diffusion medium and the MEA of the PEM hydrogen production electrolyzer.
[0028] Since pressure-sensitive paper is usually unable to measure pressure during the operation of PEMEC, the present invention introduces transparent PEMEC to observe the local performance of the electrolyzer during operation. Comparison of the two-dimensional pressure diagram of the electrolyzer and the two-phase flow state diagram under different torques Figure 3 (HN) and Figure 3 (hn) shown. Figure 3 (HN) is the two-dimensional diagram of the contact pressure between the gas diffusion medium and the membrane of the electrolyzer, Figure 3 (hn) is the two-phase flow state diagram on the anode side at 1.5 s after the electrolytic cell is powered on, Figure 3 (HN) and Figure 3 (hn) one-to-one correspondence. Figure 3 As shown in (H), at 2 N·m, due to the low bolt torque, the contact pressure between the parts is unevenly distributed, resulting in poor performance. Figure 3 (h) shows that at 2 N·m, bubbles are extremely rare and almost no bubbles are generated in the central area, so the two-phase flow photos can be compared with the pressure-sensitive paper results. Figure 3 (HK) and Figure 3 As shown in (hk), as the bolt torque continues to increase, the pressure distribution in the two-dimensional image of the pressure-sensitive paper gradually becomes uniform, and the bubble generation area reaches the highest at 3.5 N·m. However, since higher bolt torque will compress the porous diffusion layer, causing the porosity to decrease and the performance to deteriorate, when the bolt torque exceeds 3.5 N·m, the bubble generation sites gradually decrease and the bubble coverage area gradually decreases, as shown in Figure 2. Figure 3(kn). In summary, the analysis results show that the contact pressure distribution becomes more uniform as the bolt torque increases, but higher bolt torque causes changes in the diffusion layer structure, resulting in obstruction of water transport, which in turn causes a decrease in electrochemical performance. Overall, when the bolt torque is 3.5 N·m, the bubble coverage is the densest, and the electrochemical performance is the best at this time.
[0029] S7: To analyze the relationship between bolt torque and the overall electrochemical performance of PEMEC, polarization curves were measured for different bolt torques, such as Figure 4 shown. Figure 4 The results show that the PEMEC voltage increases with the increase of current density. In addition, the polarization curve characteristics corresponding to different bolt torques are different. Overall, at low current density (<0.8 A / cm 2 ), the polarization curves of different bolt torques basically do not change much. This is mainly because the change of bolt torque mainly affects the contact resistance. When the current density is low, the reversible voltage and activation overpotential account for a high proportion in the polarization, while the affected mass transfer overpotential and ohmic overpotential have little effect at low current density. However, with the continuous increase of current density, the difference between different bolt torques also increases. At high current density, when the bolt torque is 2 N·m and 5 N·m, the corresponding PEMEC voltage is significantly higher than the PEMEC voltage corresponding to other torques. The voltages of bolt torques of 2 N·m and 5 N·m are significantly higher than other voltages, but the principles of the two voltage increases are different. The polarization curve with a bolt torque of 2 N·m is due to the uneven distribution of contact pressure, which significantly increases the contact resistance, resulting in a higher ohmic overpotential at high current density; while the polarization curve with a bolt torque of 5 N·m is due to the decrease in the porosity of the porous layer, resulting in a higher mass transfer overpotential at high current density. Therefore, the polarization curve of 2 N·m is relatively linear, while the polarization curve of 5 N·m is relatively curved. From Figure 5 It can be seen that among the different torques, the polarization curve of 3.5 N·m is the lowest, which represents the best electrochemical performance, which is mainly the result of the combined influence of contact resistance and porosity of the porous layer.
[0030] The results show that when the bolt torque increases from 2 N·m, the two phenomena of the decrease of ohmic overpotential and the increase of mass transfer overpotential coexist. Before reaching 3.5 N·m, the decrease of ohmic overpotential has a more obvious effect on the overall performance of the electrolyzer, and the overall performance of PEMEC continues to improve; after exceeding 3.5 N·m, the increase of mass transfer overpotential has a more obvious effect on the overall performance of the electrolyzer, and the overall performance of PEMEC continues to decline. Therefore, the PEMEC used in this experiment has an optimal bolt torque of 3.5 N·m.
[0031] S8: In order to study the effect of different tightening steps on electrolytic performance and pressure distribution uniformity, this section will set up five tightening methods: single-step tightening, two-step tightening, three-step tightening, four-step tightening and five-step tightening. The bolt numbers and bolt tightening sequence used in the experiment are as follows: Figure 5 As shown in the figure, the bolt tightening sequence is 2-7-4-5-1-8-3-6. The tightening steps used in the experiment are defined as follows: Figure 6 shown.
[0032] The target torque of this test is set to 3.5 N·m, and the Figure 5 The contact pressure between the gas diffusion medium and MEA of the electrolyzer under different tightening methods was recorded with pressure-sensitive paper, and after image conversion, a three-dimensional pressure diagram of the electrolyzer was obtained, as shown in the figure: Figure 7 (AD) As shown. Among them, the single-step installation is worse than other methods in terms of pressure uniformity. This is mainly because the single-step installation is to directly tighten each bolt to the target torque, so the end plates on both sides of the PEMEC cannot always remain parallel during the installation process, which ultimately leads to poor uniformity of pressure distribution in the single-step tightening method. Figure 7 (AD) It can be seen that as the number of tightening increases, the pressure distribution gradually becomes uniform. Figure 7 (C) and Figure 7 (D) It was found that there was not much difference between the three-step tightening and the four-step tightening methods, which means that the contact pressure does not increase indefinitely with the increase of tightening times.
[0033] The two-dimensional pressure diagram and two-phase flow state diagram of PEMEC at different tightening steps are shown in the figure. Figure 7 (EH) and Figure 7 (eh). Figure 7 (E) It can be seen that there is a large cavity in the center of the electrolytic cell, and Figure 7 In (F), the central void is relatively reduced. Figure 7 (EH) found that three-step tightening and four-step tightening are much better than single-step tightening and two-step tightening in terms of pressure distribution uniformity. Figure 7 (G) Figure 7 In (H), the shape of the central cavity is slightly different, but the area occupied is basically the same. The contact area is the same, so the performance of three-step tightening and four-step tightening is relatively similar. Figure 7(eh) It can be seen that the two-phase flow visualization photos of PEMEC with different tightening steps can well confirm the above viewpoints. The bubbles generated by three-step tightening and four-step tightening are more than those generated by single-step tightening and two-step tightening. This is mainly due to two reasons: on the one hand, with the increase in the number of tightening steps, the pressure of the two end plates can remain parallel during the installation process, and the pressure distribution is relatively uniform; on the other hand, the water in the proton exchange membrane around the first tightened bolts is squeezed to other places, resulting in uneven water distribution in the proton exchange membrane. Uneven water distribution in the membrane will cause uneven local conductivity of the membrane, and thus the performance will be reduced. However, as PEMEC is flushed for a long time, the water distribution in the membrane will gradually return to uniformity. In summary, the experimental results show that with the increase in the number of bolt tightening steps, the local performance of the electrolyzer shows an upward trend. When the number of steps exceeds three, the improvement of the local performance of the electrolyzer is no longer obvious.
[0034] S9: To study the effect of tightening steps on the integrity of PEMEC, the electrochemical performance tests were carried out under different tightening steps at a temperature of 60 °C and a flow rate of 10 mL / min. The polarization curves of PEMEC were finally obtained as shown in Figure 8 As shown. Figure 8 It can be seen that the PEMEC voltage is the highest during single-step tightening, indicating that the PEMEC performance is the worst during single-step tightening. This is mainly caused by poor contact caused by single-step tightening. As the number of steps increases, the voltage of PEMEC gradually decreases. However, overall, the performance of PEMEC increases significantly during the process from single-step tightening to two-step tightening. However, as the number of tightening steps increases, the room for improvement in PEMEC performance gradually decreases. The polarization curves of three-step tightening and four-step tightening are basically the same. To prove this, the experiment added five-step tightening, and it was found that the polarization curve of the electrolyzer basically coincided with that of four-step tightening, and the degree of improvement was not large compared with three-step tightening. Therefore, considering the convenience of installation, three-step tightening is the best choice.
[0035] S10: In order to study the effect of different tightening sequences on the performance of the electrolyzer, five most common tightening sequence schemes were designed, namely diagonal tightening, clockwise tightening, tightening from left to right, tightening from the middle to the diagonal, and star tightening. The specific sequence is as follows Fig. 9 and Fig.10 shown.
[0036] The test set the target torque to 3.5 N·m, and used a three-step tightening method to install the electrolyzer according to five bolt tightening sequences. The contact pressure between the gas diffusion medium and the MEA of the electrolyzer under different tightening methods was recorded with pressure-sensitive paper, and after image conversion, a three-dimensional pressure map of the electrolyzer was obtained, as shown in Figure 2. Fig.11 (AE) shown. Fig.11(AE) It can be seen that when using Scheme D, the pressure area of MEA is the largest and the force is the most uniform. In this case, the contact resistance of the electrolyzer is the smallest. The second smallest contact resistance is Scheme A. This is mainly because the distance from the middle bolts (bolts numbered 2, 7, 4, 5) to the center is smaller than the distance from the diagonal bolts (bolts numbered 1, 8, 3, 6) to the center. When the middle bolts are tightened first and the diagonal bolts are tightened later (Scheme D), all 8 bolts can maintain sufficient preload. However, when the diagonal bolts are tightened first and the middle bolts are tightened later (Scheme A), the diagonal bolts tightened first will loosen, thereby reducing the overall preload. Scheme E takes into account both the diagonal and middle bolts, so uniform contact is obtained around the gas diffusion layer, but there is a large area of poor contact in the middle. The worst tightening sequence is Scheme C, which also has the possibility of sealing failure. This is mainly because the operation process of Scheme C significantly changes the uniformity of contact pressure distribution and the uniformity of water distribution in the proton exchange membrane.
[0037] During the bolt tightening process, the electrolytic cell end plate will undergo elastic deformation, and the deformation state and deformation amount are closely related to the bolt tightening sequence. In the operation process of Scheme A, the four diagonal bolts (bolts numbered 1, 8, 3, and 6) are tightened first, which will cause the end plate to form an arch-shaped elastic deformation with a raised middle. In this case, applying the target torque to the four middle bolts (bolts numbered 2, 7, 4, and 5) will make it difficult to overcome the arch-shaped deformation and restore the end plate to flatness. Therefore, the actual clamping pressure generated in the middle is small, and the clamping pressure is concentrated at the four corners. Fig.11 (A) As shown. In the operation of Scheme D, the middle bolt is tightened first, and the end plate forms an anti-arch bridge deformation. Then, when the four screws at the diagonal are tightened, although there is a tendency to produce an arch bridge deformation, the middle bolt has been tightened, which suppresses this deformation tendency and the deformation of the end plate is relatively small (see Fig.11 (D)), so compared with Scheme A, the tightening sequence of Scheme D makes the force uniformity of MEA better. The operation of Scheme E makes the formation and suppression of arch bridge deformation alternate, making the arch bridge deformation area a more regular circle, and the installation effect is close to Scheme A and Scheme D (see Fig.11 (E)). Fig.11 (BC) It can be seen that both Scheme B and Scheme C tightening sequences have severe pressure concentration and large deformation of the end plate. This is because a large pressure is first applied to one side of the end plate during installation, causing severe seesaw-like deformation of the end plate. Applying the target torque to the bolts behind makes it difficult to overcome the seesaw-like deformation and restore the end plate to flatness.
[0038] The two-dimensional pressure diagram and two-phase flow state diagram of the electrolytic cell under different tightening sequences are shown in the figure. Fig.11 (FJ) and Fig.11 (fj) is shown. Fig.11(FJ) It can be seen that among the five installation sequences, Scheme D makes the contact area between MEA and the diffusion layer the largest, the contact resistance the lowest, and the installation effect the best. Comparison of the two-dimensional pressure distribution diagram ( Fig.11 (FJ)) and bubble distribution diagram ( Fig.11 (fj)), it is found that the bubbles are densely distributed in the high contact pressure area, while the bubbles are sparse in the lower pressure area. Fig.11 (fj), it is found that under the installation method of scheme D, the number of bubble generation sites is the largest, the number of bubbles generated is the largest, and the reaction is the most intense, so this installation sequence is the most effective.
[0039] Under the conditions of water temperature of 60 ℃ and flow rate of 10 mL / min, the polarization curves corresponding to different tightening sequences are as follows: Fig.12 As shown. At 0-1.3 A / cm 2 Within the range, the polarization curves corresponding to each tightening sequence are close, and the voltage difference between the best performance and the worst performance is only 2.5%, indicating that at low and medium current densities, the effect of the bolt installation sequence on the electrolytic performance is generally small. However, at high current density, the bolt installation sequence has a significant effect on the electrolytic performance. Among them, Scheme D has a good performance at 1.3-2 A / cm 2 The process has the lowest polarization and therefore has the best performance. Although Scheme E has a lower polarization than Scheme A, the difference is smaller, only 1.1%. Fig.12 (f) and Fig.12 (i) Two-phase flow state, it can be seen that scheme E produces fewer bubbles, and they are more concentrated around the flow channel. Therefore, when considering polarization and two-phase flow state at the same time, scheme A is better than scheme E, which also shows that polarization is not the only criterion for evaluating the performance of the electrolytic cell. Among the five installation sequences of the electrolytic cell bolts, the performance of the installation from the middle to the diagonal (scheme D) is the best, and the performance of the diagonal installation (scheme A) is second. Combined with the analysis of the results of pressure-sensitive paper, it is shown that the electrolytic performance of the electrolytic cell bolts is good when installed according to the principle of symmetry, and the four middle bolts are the most important bolts for fixing the electrolytic cell. The main reason is that the four middle bolts suppress the arch-shaped deformation of the end plate and reduce the deformation; the installation according to the principle of symmetry makes the force distribution of the various components of the electrolytic cell uniform, the gas diffusion layer of the electrolytic cell has good contact with the MEA, the contact resistance is small, and the electrolytic performance is improved. In particular, the installation method according to the principle of symmetry is conducive to uniform pressure, and the four middle bolts are the most important fastening bolts of the electrolytic cell.
[0040] The research conclusions are summarized as follows:
[0041] (1) The clamping pressure of PEMEC increases with the increase of bolt torque. The increase of bolt torque reduces the contact resistance between the various parts of PEMEC, thus improving the performance. However, when the MEA and the diffusion layer are subjected to excessive pressure, the gas-liquid transport channel inside the diffusion layer is deformed, which hinders the gas-liquid exchange process; at the same time, the membrane electrode is also over-extruded, which has a certain impact on the mass transfer process. The two effects work together to increase the mass transfer overpotential of the electrolyzer. The experimental results prove that the two processes of reducing the ohmic overpotential and increasing the mass transfer overpotential exist simultaneously, and it is found that PEMEC has an optimal torque.
[0042] (2) Splitting the same torque into multiple steps for tightening is conducive to uniform clamping pressure. This is mainly because during the bolt tightening process, the bolts tightened later cause the end plate and gasket to deform, causing the bolts tightened first to loosen to a certain extent. Therefore, during single-step tightening, the pre-tightening torque of the first tightened bolt is significantly reduced. At this time, the pressure at the MEA is the smallest and the most uneven, and multi-step tightening can improve this phenomenon. However, the effect of multi-step tightening on improving the performance of the electrolyzer is limited. Compared with the three-step tightening, the performance improvement of the electrolyzer is not obvious. Therefore, considering the convenience of installation and time cost, using three-step tightening is the best choice.
[0043] (3) Different tightening sequences affect the electrochemical performance of PEMEC. The present invention compares five tightening sequences: diagonal tightening, clockwise tightening, tightening from left to right, tightening from the middle to the diagonal, and star tightening. The experimental results show that the cross-symmetrical installation sequence can make the end plate load evenly distributed (such as Scheme A and Scheme D), and tightening from the middle to the diagonal (Scheme D) can reduce the deformation of the end plate, further improve the force uniformity of MEA, and have the best performance.
Claims
1. An experimental research method for exploring the influence of bolt tightening behavior on the performance of a proton exchange membrane electrolyzer based on a transparent visualization system, characterized in that: The following steps are involved: S1: First, the pressure distribution between the gas diffusion layer and MEA of PEMEC under different experimental conditions was measured by pressure-sensitive paper. The pressure map of the pressure-sensitive paper was converted into two-dimensional and three-dimensional pressure cloud maps using high-definition scanners and image processing technology. The effects of bolt torque, tightening steps, and tightening sequence on the contact resistance of PEMEC were studied through three-dimensional pressure cloud maps. S2: Intercept the two-phase flow distribution generated by the high-speed camera in the same time period, combine it with the two-dimensional pressure cloud map, and verify the influence of bolt torque, tightening steps, and tightening sequence on the electrochemical performance of PEMEC; S3: Based on the above research, the current density and voltage of the whole PEMEC are measured, the PEMEC polarization curve is drawn, and then the optimal torque, the most appropriate number of tightening steps, and the most appropriate tightening sequence of the bolt are determined based on the experimental data.
2. The experimental research method for exploring the influence of bolt tightening behavior on the performance of PEMEC based on a transparent visualization system according to claim 1 is characterized in that: The experimental test bench is composed of: PEMEC, water bath, peristaltic pump, high-speed camera, power supply, digital torque wrench and gas-liquid separator, and data collection and parameter control can be performed through the host computer.
3. The experimental research method for exploring the influence of bolt tightening behavior on the performance of PEMEC based on a transparent visualization system according to claim 1 is characterized in that: In S1, the pressure distribution measurement is mainly achieved by visualizing the local pressure through pressure-sensitive paper. The pressure-sensitive paper used in the experiment has a measuring range of 0-5 MPa and a thickness of about 0.2 mm, which can be a good substitute for the membrane electrode.
4. The experimental research method for exploring the influence of bolt tightening behavior on the performance of PEMEC based on a transparent visualization system according to claim 1 is characterized in that: In the S2, the high-speed camera used in the experiment has 240 fps and 1.3 million pixels, which is used to record the bubbles and bubble distribution during the torque experiment.
5. The experimental research method for exploring the influence of bolt tightening behavior on the performance of PEMEC based on a transparent visualization system according to claim 2, characterized in that: The visualized PEMEC is composed of the following components: end plates, transparent plates, current collectors, diffusion layers, membrane electrodes, bolts, gaskets, etc., which are fixed by 8 symmetrically distributed M6 hexagonal bolts.
6. The experimental research method for exploring the influence of bolt tightening behavior on the performance of PEMEC based on a transparent visualization system according to claim 2, characterized in that: The water bath was used to control the temperature of the circulating water. The experiment used a HH-2 double-hole model with a heating temperature range of 10°C-100°C and a temperature fluctuation of less than 0.1°C. A peristaltic pump, model BT100, is used to provide water flow input for PEMEC, with a flow range of 0.002-570 mL / min. A digital torque wrench, model KPD-10, is used to adjust the bolt torque, with a working range of 0.5-10 N·m and an accuracy of ±0.1 N·m. The system power supply is a programmable DC power supply, model SS-K1560SP 15V 60A, with an output voltage of 0-15V, a voltage resolution of 1 mV, an output current of 0-60A, and a current resolution of 1 mA. To ensure the normal operation of PEMEC, water will be passed through the anode and cathode at the same time. The gas-liquid separator can separate the gas-liquid mixture discharged from PEMEC, and the liquid will flow back to the water bath for circulation.
7. The experimental research method for exploring the influence of bolt tightening behavior on the performance of PEMEC based on a transparent visualization system according to claim 5, characterized in that: The bolts are made of SCM435 alloy steel with a tensile strength of 1220MPa, a nominal torque of 15-20N·m, and a standard verification load of 830MPa. The PEMEC end plate is made of stainless steel with an observation window. The end plate size is 100 mm×100 mm, and the observation window size is 50 mm×50 mm. The transparent plate is made of acrylic plate material. Through the observation window on the end plate, the gas-liquid two-phase flow state in the electrolyzer can be observed through the transparent plate. The current collector is made of mirror-finished pure titanium plate, which has good corrosion resistance and electrical conductivity. A serpentine flow channel with a width of 1 mm is engraved on the titanium plate. Titanium felt is used as the gas diffusion layer of the cathode and anode, in which the anode side has a 0.5 μm thick iridium coating and the cathode side has a 0.5 μm thick platinum coating. The proton exchange membrane uses Nafion117 membrane with a membrane size of 50 mm×50 mm×0.17 mm, and the anode side and cathode side are respectively 2.0 mg / cm 2 Iridium dioxide (IrO2) and 2.5 mg / cm 2 of platinum (Pt) as a catalyst.